Development of methods for separation of binarized fragments of etching pits of semiconductor wafer - Самойлов, Андрей Николаевич; Шевченко, Игорь Васильевич (Technology audit and production reserves, 2016)
The article is devoted to the search of successful methods for separation of fragments belonging to the supposed etching pits of dislocation loops. The developed methods are revealed binarized fragments of etching pits among of the many other elements of surface image of a semiconductor wafer. The filtration method of binarized fragments of etching pits of wafer dislocation uses a roundness index of the specified range, received on the base of reference line width of dislocation loop at a ratio of 1:4. This optional feature allows separating fragments similar to lines of loops of etching pits on the basis of their size and shape. The method of removing the micro-defects loops reduces the number of fragments by eliminating of loops without signs of loops of etching pits. It is based on the use of the XOR subtraction operation between the binarized image of dislocation areas and the image with accentuated loops of the fragments. The criteria for allocation of the main significant loop fragments allow form the selection rules for the further processing of binarized image. The criteria for allocation of the main significant loop fragments, method of binarized fragments filtering, method of removing the loops of micro-defects of the semiconductor wafer are the part of a package of measures to carry out tasks on production management organization and creation of technical diagnostic system of output production quality.